Specific educational program for adolescent anemia prevention (Progres MIRA) to adolescent girls in remote areas of Bengkulu, Indonesia - Sri Yanniarti; Epti Yorita; Erika Yulita; Tengku Sri Wahyuni (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Anemia prevalence worldwide ranges from 30-50%, mostly occurring in developing countries, predominantly affecting adolescent groups. In Indonesia, the prevalence of anemia in females aged ≥15 years is 22.7%. Cases in Indonesia include 45% in Denpasar City and 62% in Bengkulu Province. Generally, adolescent girls are vulnerable to anemia due to significant blood loss during menstruation, posing risks of Low Birth Weight (LBW) and stunting during childbirth.Purpose: To determine the effectiveness of Progres MIRA (Specific Education Program for Anemia Prevention in Adolescents) on compliance with iron supplement consumption and hemoglobin levels in adolescent girls on Enggano Island, North Bengkulu Regency in 2023.Method: This study used a quasi-experimental post-test only method with a control group. The Progres MIRA research intervention involved a specific education program for anemia prevention in a special classroom setting. The independent variable was Progres MIRA, the dependent variables were hemoglobin levels and compliance with consuming iron supplement tablets, and external variables included menstrual duration, menstrual cycle, nutrient intake, and economic status.Results: The research findings showed that 82.9% of adolescent girls had a menstrual duration of >6 days, which influenced the amount of iron supplement tablet consumption among them. The menarche age among adolescent girls in the Progres MIRA group was 28.6% at an age <12 years. Compliance levels in treatment related to the menstrual duration variable obtained a ρ-value= 0.01, menarche age obtained a ρ-value= 0.57, malnutrition deficiency index obtained a ρ-value= 0.04, and MUAC obtained a ρ-value= 0.10. This indicates that Progres MIRA effectively increases compliance with iron supplement tablet consumption among adolescent girls.Conclusion: Progres MIRA is effective in improving compliance with iron supplement tablet consumption among adolescent girls. Recommended Dietary Allowance (RDA) significantly affects compliance with iron supplement tablet consumption among adolescent girls.